Care leavers' views about transition: a literature review. Issue 1 (26th March 2019) - Atkinson, Cathy; Hyde, Rebekah
Abstract : Purpose: Considerable attention has been given to the vulnerability of young people leaving care in the UK in their transition to adulthood. To date, however, there has been limited focus on the perceptions of care leavers about what factors enable and inhibit effective practice. The paper aims to discuss these issues. Design/methodology/approach: This systematic literature review sought to elicit the views of UK care leavers in identifying barriers and facilitators to the process of transition to adulthood. Qualitative studies in the care-leaving field were identified, of which seven met inclusion criteria and were included in the final synthesis. Findings: The findings yielded a range of facilitators, including authentic and consistent relationships with those acting in the role of corporate parent; and flexible systems, which accommodated personal readiness for leaving care. Barriers included insufficient recognition of, and a lack of support for, the psychological dimensions of transition, exacerbated by insufficient support networks. Research limitations/implications: This literature search yielded seven qualitative papers, some with small sample sizes, meaning that the findings may not be representative of a wider population or directly relevant to international contexts. Practical implications: Suggestions for enhancing the transition process are posited. In particular, the potential usefulness of an "interdependence" transition approach for UK care leavers is proposed. Originality/value: This study analyses qualitative data, thus constituting a response to policy calls for care leaver views to be central to transition processes.